2020
DOI: 10.1111/ajgw.12462
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines and the importance of starter cultures for malolactic fermentation

Abstract: Biogenic amines are compounds produced mainly by microorganisms from the decarboxylation of some amino acids which may cause several health issues in susceptible people. In the winemaking process, one of the factors with the greatest impact on the final concentration of biogenic amines in wine is the malolactic fermentation, which mainly involves the action of lactic acid bacteria. This article gathers scientific literature on the importance of the use of inoculation in winemaking, especially for the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…content in seven different grape varieties under sterile conditions, except for agmatine [ 20 , 21 ]. It is well documented that the concentration and nature of B.A.s present found in wines, in general, depend mainly on the composition of the grape juice in literature by many authors [ 22 , 23 , 24 ]; however, we observed the lack of a synthesis study regarding the effect of B.A.s on quality characteristics throughout berry ripeness in grape varieties with foxy and muscat taste. As mentioned above, although there are many lines of research examining BAs in grapes and grape-derived products, there are still many possibilities to explore from microbiological, technological, analytical, and toxicological perspectives.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…content in seven different grape varieties under sterile conditions, except for agmatine [ 20 , 21 ]. It is well documented that the concentration and nature of B.A.s present found in wines, in general, depend mainly on the composition of the grape juice in literature by many authors [ 22 , 23 , 24 ]; however, we observed the lack of a synthesis study regarding the effect of B.A.s on quality characteristics throughout berry ripeness in grape varieties with foxy and muscat taste. As mentioned above, although there are many lines of research examining BAs in grapes and grape-derived products, there are still many possibilities to explore from microbiological, technological, analytical, and toxicological perspectives.…”
Section: Introductionmentioning
confidence: 59%
“…Although there have been new approaches and reports on a wide range of functions of B.A.s in wine and table grapes in the last few decades [ 4 , 22 , 26 ], to our knowledge, information on the reactions of B.A. both in grape varieties containing foxy and muscat taste and in berry ripeness stages has yet to be revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review is intended to summarize different types of biogenic amines in food and biological systems, their functions, and strategies to control the amount with a focus on the use functional ingredients and food-related bioactive compounds. This is different from other reviews that focus on the control of BAs using mostly temperature, antimicrobials, irradiation, high hydrostatic pressure, starter culture, or non-producing decarboxylating microorganisms [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 77%
“…From the managerial perspective, other studies delved into the impact of specific production conditions and winemaking techniques on wine quality [ 155 , 156 ]. As in the previous period, studies analysed the relationship between wine quality and price [ 157 , 158 ].…”
Section: Resultsmentioning
confidence: 99%